Acute Poisoning Cases Presented to the Addis Ababa Burn, Emergency, and Trauma Hospital Emergency Department, Addis Ababa, Ethiopia: A Cross-Sectional Study - Biruktawit Zemedie; Menbeu Sultan; Ayalew Zewdie (Emergency Medicine International)
Background. Acute poisoning is a common reason for visits to the emergency room and hospitalization across the world, as well as a possible cause of morbidity and death. This study aimed to assess acute poisonings at Addis Ababa Burn, Emergency, and Trauma (AaBET) Hospital. Methodology. A one-year cross-sectional study was conducted at AaBET Hospital from February 1, 2018, to January 31, 2019. Data were collected using a structured and pretested questionnaire by the Emergency Medicine and Critical Care residents from acutely poisoned patients’ interviews and patient charts. Results. Data were collected from 98 acute poisoning cases, and 52% were males and 48% were females. 85 (86.7%) were less than 45 years. 52 (55.1%) were unemployed, and 33 (33.7%) were farmers. 96 (98%) cases were due to intentional poisoning, and 96 (98%) had oral ingestion. Organophosphates poisoning (27.5%) was the commonest cause, followed by 26.5% of unknown poisons and 16.3% prescribed drugs. Sixty-six percent of the patients presented to the hospital after 2 hours of ingestion. The case fatalities were 10.2% of which 40% of the cases were due to 2,4-dichlorophenoxyacetic (2, 4-D) poisoning, followed by aluminum phosphide (20%). Conclusion. This study showed farmers and the unemployed were more affected. The most common mode of poisoning was intentional poisoning, oral ingestion being the primary route. The common poisons used by the victims were organophosphates. 2, 4-D poisoning was the major cause of death.